Evaluation of scale-adaptive simulation for transonic cavity flows. (2016) - Babu, Savio V.; Zografakis, George; Barakos, George N.; Kusyumov, Alexander
Scale-adaptive simulations of transonic cavities with and without doors are presented in this paper. Results were compared with detached-eddy simulations for cavities with length-to-depth ratios of 5 and 7. The Mach and Reynolds numbers (based on the cavity length) were 0.85 and 6.5 × 106, respectively, and the grid sizes were 5.0 million for the clean cavity with doors-off and 5.5 million for the clean cavity with doors-on. Instantaneous Mach number contours showed that the shear layer broke down for both the doors on and doors off cases and that the flows had a high level of unsteadiness inside them. The two L/D ratios of cavities were seen to have similar acoustic signatures reaching maximum sound levels of 170 dB. Spectral analyses for the cavities without doors revealed that by changing the length-to-depth ratio from five to seven, the dominant acoustic modes at the front and rear of the cavities were shifted from the second and third modes to the first and second modes respectively. Proper orthogonal decomposition was used to reduce the data storage using modes constructed from flowfield snapshots taken at regular intervals.